THERMAL DEGRADATION BEHAVIOUR OF CARBON FIBRE WASTE AS A FILLER IN POLYMER HYBRID COMPOSITES - MOHAMMAD, SYAZWAN FIKRI (IRC, 2020)
Carbon Fiber and Glass Fiber Reinforced Polypropylene (CFGFRP) is a hybrid polymer composite has been one of crucial material in many modern products. Nevertheless, there are several downsides of CF which degrading its astonishing mechanical properties, hardening the material, and reduce material flexibility. Therefore, recycled Carbon Fiber and recycled Glass Fiber Reinforced Polypropylene (rCFrGFRP) is an initiative for future cost saving during production. In this paper (rCF/rGF/PP) hybrid polymer composites were prepared under injection moulding process. The thermal degradation behaviour of this composite was investigated considering the combined effect of rCF and rGF on PP matrix via thermogravimetric analysis (TGA) and oven heating process. Hardness tests were taken to investigate mechanical properties effect of the composite. Finally, these can be showing the combination effect of rCF and rGF on thermal degradation of the composite.